Karakteristik Fisikokimia dan Organolpetik Produk Chifon Cake Berbahan Dasar Tepung Sagu (Metroxylon sp.) Termodifikasi - Wahyuni, Sri; Khaeruni, Andi; Elvira, Ilian; Dahlan, Andi; Fatahu, Fatahu; Usnul F, Maysya Sarwa (Agroindustrial Technology, University of Trunojoyo Madura, 2025)
The aim of this research was to determine the effect of using modified sago flour resulting from fermentation using lactic acid bacteria (BAL) UM 24, the heat moisture treatment (HMT) process and the combination of BAL UM 24 and HMT fermentation on the organoleptic and physicochemical characteristics of chiffon cake. This research used a Completely Randomized Design (CRD). The data analysis used was the ANOVA test and further test (T test) at the 95% confidence level (α=0.05). The results of the chiffon cake physical test research, the selected flour modification treatment can increase the kamba density and water absorption capacity of the chiffon cake, as well as reduce the specific volume of the chiffon cake. The selected treatment for the organoleptic test is the sago flour modification treatment with BAL UM 24 fermentation with a color preference score. , aroma, taste and texture of chiffon cake. respectively 4.15 (like), 4.20 (like), 4.13 (like), 4.10 (like). The physical characteristics of the selected treatment were a specific volume value of 21.68 (ml/g), a kamba density of 56.08 (g/ml) and a water absorption capacity of 1.27 (%). Proximate content with water content of 27.24 (% wb), ash content 1.33 (% db), protein content 13.39 (% db), fat content 17.16 (% db) and carbohydrates 28.24 (% db ).